Impact of the Free Nutritional Meal Program(MBG) on Students at MTs Ma’arif Pinrang Regency - Nursuciyani Jamal; Andi Sri Adinda (Golden Ratio of Data in Summary, 2026)
The Free Nutritious Meal Program, also known as the Free Lunch Program, is funded at IDR 10,000 per portion for large servings and IDR 8,000 per portion for small servings at each Nutrition Fulfillment Service Unit (SPPG) across Indonesia. The allocated cost per portion reflects a food package that includes staple foods (carbohydrates), animal protein, vegetable protein, vegetables, fruits, and milk. This free nutritious meal program serves not only as a health intervention but also as part of a broader social, economic, and educational development strategy. This study employs a quantitative cross-sectional research approach, which aims to identify and describe phenomena or factors influencing the relationship between independent (free) variables and dependent (bound) variables. The findings indicate that the impact of providing free nutritious meals through the nutrition fulfillment service units has not yet been optimal, particularly in terms of menu variation.